2013
DOI: 10.1111/eth.12133
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of Host Female and Male Aggression Towards a Brood Parasite

Abstract: Current research on behavioural consistency showed that various types of animal behaviour are highly repeatable in the context of mate choice, exploration and parental care, including nest protection. However, the repeatability of aggressive nest defence has not yet been studied in hosts of brood parasites, although host aggression against adult parasites represents a crucial line of antiparasitic defences. Here, we investigated the between‐season repeatability of the great reed warbler (Acrocephalus arundinac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 78 publications
(185 reference statements)
2
12
0
Order By: Relevance
“…Interestingly, chip production for yellow warblers in general also varied over the breeding season for some treatments, with significantly more chip calls being produced toward blue jay playbacks later in the season, and less chip calls toward cowbirds. Similar patterns have been observed in other alarm‐calling species from nest predator (see Montgomerie & Weatherhead, 1988, for review) and brood parasite (Brooke et al., 1998; Trnka et al., 2013) presentation studies. These responses may be due to lower benefits of renesting later in season and the typically reduced parasitism pressure over time (Montgomerie & Weatherhead, 1988; Trnka et al., 2013).…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, chip production for yellow warblers in general also varied over the breeding season for some treatments, with significantly more chip calls being produced toward blue jay playbacks later in the season, and less chip calls toward cowbirds. Similar patterns have been observed in other alarm‐calling species from nest predator (see Montgomerie & Weatherhead, 1988, for review) and brood parasite (Brooke et al., 1998; Trnka et al., 2013) presentation studies. These responses may be due to lower benefits of renesting later in season and the typically reduced parasitism pressure over time (Montgomerie & Weatherhead, 1988; Trnka et al., 2013).…”
Section: Discussionsupporting
confidence: 76%
“…The most common of these threats comes from predators, to which parents often defend against using a variety of aggressive behaviours, from mobbing and alarm calling in avian species ( Hollander, Van Overveld, Tokka, & Matthysen, 2008 ; Redondo & Carranza, 1989 ; Wiklund, 1990 ), to biting and lunging in fish ( Itzkowitz, 1985 ; Ridgway, 1988 ), to striking and grabbing with chelae in crayfish ( Figler, Blank, & Peeke, 2001 ; Martin & Moore, 2010 ). Similar behaviours are used to counter other biotic threats such infanticidal females ( Wolff & Peterson, 1998 ) and brood parasites ( Trnka, Požgayová, Samaš, & Honza, 2013 ). Defending against these threats yields obvious fitness benefits in the form of offspring survival, yet comes at a potential cost of injury or death to parents.…”
mentioning
confidence: 99%
“…Such individual differences may also occur in the context of nest defence, whereby some individuals invest more in protecting their offspring than others ( Burtka & Grindstaff, 2013 ). Recently, a number of studies on avian species have demonstrated such individual differences in behavioural nest defences, measured by repeatability, whereby individual females are consistent across breeding seasons in how intensely they defend their nests ( Burtka & Grindstaff, 2013 ; Hollander et al, 2008 ; Trnka et al, 2013 ). This raises the question of how those individuals who consistently invest less in behavioural defence compensate for the potential fitness losses.…”
mentioning
confidence: 99%
“…We tested for antipredator behaviours that instead resulted as enemy-specific responses in yellow 32 and reed 33 warblers (Supplementary Table 1 ). Model presentations conducted within the above-cited investigations are part of a long-used field-experimental technique, largely shown to be a reliable test to discriminate abilities and information transfer (Supplementary Methods) 12 , 16 , 32 , 50 .…”
Section: Methodsmentioning
confidence: 99%